Multicultural citizenship a liberal theory of minority rights - Kymlicka, Will 1962- (Oxford political theory, 1995)
However, Professor Kymlicka emphasizes that no single formula can be applied to all groups, and that the needs and aspirations of immigrants are very different from those of indigenous peoples and national minorities. The book discusses issues such as language rights, group representation, land claims, federalism, and secession - issues which are central to understanding multicultural politics, but which have been surprisingly neglected in contemporary liberal theory